Evaluating the environmental impacts of conventional and organic apple production in Nova Scotia, Canada, through life cycle assessment. (1st October 2015) - Keyes, Sarah; Tyedmers, Peter; Beazley, Karen
Abstract: Life cycle assessment (LCA) was used to characterize the environmental performance and potential improvement opportunities related to conventional and organic apple systems in Nova Scotia, Canada. The goal was to quantify and evaluate resources and energy required for production, storage, and transportation, determining how each supply chain sub-system contributes to relevant global scale environmental burdens. Importantly, scenario models were constructed to explore performance improvement opportunities related to key supply chain inputs. Results indicate that up to point of harvest, the combustion of diesel fuel, production and associated field-level emissions of fertilizers (i.e. synthetic and manure), and inputs to pest and disease management were major contributors to environmental impacts on both conventional and organic orchards. Extending system boundaries to cradle-to-retail locations (both local and distal), revealed, somewhat surprisingly, that electricity needed for long-term storage resulted in substantial burdens, highlighting the problems of coal-based electricity generation in Nova Scotia. Consuming locally produced apples when in season was found to be environmentally preferable to those requiring year round storage, while transport by freight ship is more favorable than long distance transport truck delivery. Highlights: Conventional and organic apple supply chains in Nova Scotia were modeled and evaluated through LCA. On-orchards hotspots include fuels, fertilizers, and inputs and emissions of pest management. Coal-based electricity inputs led to significant contributions from storage systems. Transport via freight ship and rail is favorable over shipment of apples by transport truck.